Relation Between Cost Driven Green Kaizen and Pharmaceutical Production - Mishra, Sasanka S; Pradhan, Bibhuti B (International Journal of Psychosocial Rehabilitation, 2019)
A case study of green kaizen shows how operators and managers can use the Green Performance Map method in a drug manufacturer to engage in environmental improvements on a shopping floor. The method involves defining possibilities for development, an input-output visualizing model (to achieve a common understanding) and a cost saving strategy for intervention prioritizing (to reach strength). This paper would illustrate how operationalization is necessary to change behavior, and illustrates how cost is used to achieve environmental change. The necessary changes are enormous and have begun. In conjunction with new technology exponential development and the overall digitalization, this research find a mode of processing for the producing sector. There are people who say that they are aware of the industrial revolution for the first time in history. There are however significant differences of future manufacturing transition vs. current factories, i.e. brownfield, based upon the preconditions of each company to operate with new Greenfield factories.